Somatostatin analogs in pregnant patients with neuroendocrine tumor. Issue 10 (November 2020) - Meoni, Giulia; Giommoni, Elisa; Petreni, Paolo; Pillozzi, Serena; Mazzoni, Francesca; Pellegrini, Elisa; Brugia, Marco; Lunghi, Alice; Muto, Andrea; Antonuzzo, Lorenzo
Abstract : Somatostatine analogs (SSAs) are currently indicated in the treatment of acromegaly and neuroendocrine tumors (NETs). Actually, pregnancy in patients with acromegaly and NETs does not represent an exceptional event because reproductive behavior has changed in the last decades and patients with NETs show more frequently long-term survival. The safety profile of SSAs during pregnancy is still controversial. Concerning acromegaly, based on case reports and series, SSAs administration during pregnancy seems to be relatively well tolerated. Concerning patients with NETs, up to date only one patient with NET receiving SSA during pregnancy has been reported in literature. We report two cases of gastroenteropancreatic-NET patients receiving SSA lanreotide for the entire course of their pregnancy, with favorable outcomes for both mothers and babies. Our experience supports the possibility to continue safely SSA lanreotide during pregnancy in patients with NET.